2014
DOI: 10.1007/s10488-014-0563-3
|View full text |Cite
|
Sign up to set email alerts
|

Brief Intervention: A Promising Framework for Child and Youth Mental Health?

Abstract: There is a discrepancy between the demand for mental health treatment amongst children, young people and their carers, and the capacity of the current service system to provide evidence based interventions. Innovative models of care are required to redress this discrepancy. One such model is the single session model, which provides a single or small number of solution focused sessions targeting one or two identified problems. Single session interventions have been trialled across a range of presenting concerns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Minimal service use patterns may reflect well-known problems with client engagement in CYMHS [6870]. However, with more than half of all children falling into the Minimal pattern, this finding also supports the need for brief intervention services and walk-in clinics [7173]. In Ontario’s most recent child mental health treatment plan [74], brief services are one of seven core services to be available at all CYMHS agencies in the province.…”
Section: Discussionmentioning
confidence: 58%
“…Minimal service use patterns may reflect well-known problems with client engagement in CYMHS [6870]. However, with more than half of all children falling into the Minimal pattern, this finding also supports the need for brief intervention services and walk-in clinics [7173]. In Ontario’s most recent child mental health treatment plan [74], brief services are one of seven core services to be available at all CYMHS agencies in the province.…”
Section: Discussionmentioning
confidence: 58%
“…Fusing CBT with positive psychology may lessen psychological symptoms (e.g., anxiety, depression, and stress); however, establishing an intervention under traditional clinical judgment and treatment routine needs a long intervention duration. The lengthy intervention duration may not provide a timely treatment for students (Gee et al, 2015). Emerging evidence indicated that the single-session model has been used as an effective alternative to the lengthier interventions (Campbell, 2012).…”
Section: Discussion and Application To Practicementioning
confidence: 99%
“…This model can be used to promote changes by assisting clients to identify and target one or two key targets within a single 90-min session (Campbell, 1999; Gee, Mildred, Brann, & Taylor, 2015). The basic elemental principles of the single-session model are (a) to conduct a short-term intervention within a 90-min session by therapists and ongoing activities by clients in the time after the session; (b) to focus on one or two issues, identify strategies to modify the issues, and set therapeutic goals within the intervention; and (c) to enact the strategies and accomplish the goals after the intervention (Bloom, 2001; Gee et al, 2015). The single-session model has been used in drug addiction (Marcus, 1999), adolescent disturbances (Cooper & Archer, 1999), and family problems (Brown, 1984).…”
mentioning
confidence: 99%
“…Despite the growing evidence base to support the use of SST interventions, there have been few studies exploring how this has been implemented into routine service delivery. 9 The aim of the current study was therefore to explore the experience of sessions and the impact of participation on the young persons' functioning.…”
Section: Supporting Families and Carers To Understand Theirmentioning
confidence: 99%